Volume responsiveness assessed by passive leg raising and a fluid challenge: a critical review focused on mean systemic filling pressure. (24th November 2017) - Cooke, K.; Sharvill, R.; Sondergaard, S.; Aneman, A.
Summary: This review applied cardiovascular principles relevant to the physiology of venous return in interpreting studies on the utility of a passive leg‐raising manoeuvre to identify patients who do (responders) or do not respond to a subsequent intravenous volume challenge with an increase in cardiac output. Values for cardiac output, mean arterial and central venous pressure, and the calculated cardiovascular variables mean systemic filling pressure analogue, heart efficiency, cardiac power indexed by volume state and volume efficiency, before and after passive leg raising as well as before and after fluid volume challenge, were extracted from published studies. Eleven studies including 572 patients and 52% responders were analysed. Cardiac output increased by 12% in responders during passive leg raising and by 22% following a volume challenge. No statistically significant differences were found between responders and non‐responders in cardiac output, mean arterial or central venous pressure before the passive leg‐raising manoeuvre or the volume challenge. In contrast, the calculated mean (SD) systemic filling pressure analogue, reflecting the intravascular volume, was significantly lower in responders (14.2 (1.8) mmHg) than non‐responders (17.5 (3.4) mmHg; p = 0.007) before the passive leg‐raising manoeuvre, as well as before fluid volume challenge (14.6 (2.2) mmHg vs. 17.6 (3.5) mmHg, respectively; p = 0.02). The scalar measure volume efficiency was higher in responders at 0.35 compared with non‐responders at 0.10. Non‐responders also demonstrated deteriorating heart efficiency of −15% and cardiac power of −7% when given an intravenous fluid volume challenge. The results demonstrate that the calculation of mean systemic filling pressure analogue and derived variables can identify patients likely to respond to a fluid volume challenge and provides scalar results rather than merely a dichotomous outcome of responder or non‐responder.